Colony Transport Affects the Expression of Some Genes Related to the Apis mellifera l. Immune System - Scaloppi, Maurice F. [UNESP]; Kadri, Samir M. [UNESP]; Mendes, Daniel D. [UNESP]; Ribolla, Paulo Eduardo M. [UNESP]; Orsi, Ricardo O. [UNESP] (Universidade Estadual de Feira de Santana, 2022)
Migratory beekeeping can harm the bee colonies if not executed properly. Here, colonies of Apis mellifera were transported (for one or two hours) or not, following proper technical standards. To analyze gene expression (defensin-1, abaecin, and HSP70), forager bees were collected immediately, 24, and 72 hours after transportation. Bee mortality and population growth were measured before and after transportation. This study concludes that transporting honey bee colonies for 2 hours promotes immune system gene expression, although there are no significant changes in bee mortality and population growth of the colonies.
Keywords: Beekeeping; Colony transportation; Stress; Transportation Management; Welfare